2006
DOI: 10.3748/wjg.v12.i38.6207
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationship between chromosome 8 aneuploidy,C-MYCamplification and increased expression in individuals from northern Brazil with gastric adenocarcinoma

Abstract: Distinct patterns of alterations between intestinal and diffuse types of gastric tumors support the hypothesis that these types follow different genetic pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
66
7
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(92 citation statements)
references
References 36 publications
(31 reference statements)
17
66
7
2
Order By: Relevance
“…We have also previously seen MYC amplification in intestinal adenocarcinoma by dual-color fluorescence in situ hybridization (FISH), such as homogeneously staining chromosomal regions and double minutes, supporting our CGH results [56] . Our findings support that these two histological GC types follow different genetic pathways.…”
Section: Mechanisms Of Myc Deregulation In Gastric Cancersupporting
confidence: 88%
See 2 more Smart Citations
“…We have also previously seen MYC amplification in intestinal adenocarcinoma by dual-color fluorescence in situ hybridization (FISH), such as homogeneously staining chromosomal regions and double minutes, supporting our CGH results [56] . Our findings support that these two histological GC types follow different genetic pathways.…”
Section: Mechanisms Of Myc Deregulation In Gastric Cancersupporting
confidence: 88%
“…Yamashita et al [74] identified chromosomal translocations involved in 8q24 breakpoint by spectral karyotyping (SKY) analysis of established GC cell lines and cancerous ascitic fluids. In a previous study, our findings suggested that translocations can be related to diffusetype GC using FISH assay [37,56] . Epigenetic events play a significant role in cancer development and progression.…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…The membrane undersurface was coated with 200 µl FCS for 1 h at 37˚C and blocked with 200 µl migration buffer (0.5% BSA in DMEM) for 30 min at 37˚C. The lower chamber was filled with 500 µl of migration buffer, following which cells were plated in the upper chamber of 4 wells/treatment at a density of 1x10 5 in 100 µl of migration buffer and incubated at 37˚C for 4 h. Following incubation, cells in the upper compartment were trypsinized and counted by the CASY 1 counter (Sharfe System, Reutingen, Germany). Cells that had migrated to the lower surface of the filter were also trypsinized and counted.…”
Section: Analysis Of Transfectants Rt-pcr and Western Blot Analysismentioning
confidence: 99%
“…Currently, a number of molecular abnormalities have been identified, including the activation of oncogenes, inactivation of tumor suppressor genes, microsatellite and chromosomal instability, and alteration of growth factors and cytokines (Smith et al, 2006). Many proto-oncogenes are activated and overexpressed in gastric cancer, such as c-met (Inoue et al, 2004), c-erB2 (Song et al, 2004), K-sam (Toyokawa et al, 2009), Ras (Nishigaki et al, 2005), and c-myc (Calcagno et al, 2005). Inactivation of tumor suppressor genes due to mutations and/or loss of heterozygosity is also a frequent event in gastric carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%